Pelanggaran Lalu Lintas Berdasarkan Undang-Undang No. 22 Tahun 2009 Tentang LLAJ di Kota Gorontalo Melalui Electronic Traffic Law Enforcement (ETLE) - Lukman Oktavian Kadir; Lisnawaty W Badu; Jufryanto Puluhulawa (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research is intended to: (1) find out how effective the implementation of Electronic Traffic Law Enforcement (ETLE) is for traffic violations based on Law no. 22 of 2009 concerning Traffic in Gorontalo City. The research results show, first, the implementation of the ETLE system for traffic violations based on the LLAJ Law in Gorontalo City is to modernize the system for handling traffic violations, enforce traffic laws, and in order to instill a culture of compliance in traffic. Apart from that, the implementation of the ETLE system in Gorontalo City is quite effective and better than conventional systems because the ETLE system can produce more violation data, is efficient in terms of time, and does not require deploying officers in the field directly. Second, the factors that hinder the implementation of the ETLE system in Gorontalo City are the lack of a culture of traffic compliance by the community, a mismatch between the data held by officers and the data recorded by the ETLE system, and the ETLE system not being able to detect certain types of violations.